2018
DOI: 10.1021/acs.jafc.8b00385
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Cellulose Relieves Diphenoxylate-Induced Constipation in Rats

Abstract: This study was to probe the effects of bacterial cellulose (BC) on diphenoxylate-induced constipation in rats. Administration with BC at 500 mg/kg of body weight in diphenoxylate-induced constipation rats distinctly improved the carmine propulsion rate (83.5 ± 5.2%), shortened the defecating time of the first red feces (249.0 ± 23.3 min), and increased the weight of carmine red feces within 5 h (2.7 ± 1.3 g). The levels of aquaporins (AQP-2, AQP-3, and AQP-4) and inhibitory neurotransmitters (nitric oxide, nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 60 publications
2
36
0
1
Order By: Relevance
“…Many studies have shown that the indigestible carbohydrates of a supplement possess beneficial effects on gut health [22,23,24]. These carbohydrate supplements are mainly polysaccharides and oligosaccharides, while there are few studies about monosaccharides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that the indigestible carbohydrates of a supplement possess beneficial effects on gut health [22,23,24]. These carbohydrate supplements are mainly polysaccharides and oligosaccharides, while there are few studies about monosaccharides.…”
Section: Discussionmentioning
confidence: 99%
“…Neurotransmitter also plays an important role in gastrointestinal hormones [28]. A couple of neurotransmitters have been identified to be associated with the motor activity of the gastrointestinal tract, such as Ach, NO, SP, and VIP, which play important roles in the regulation of gastrointestinal motility [14,24,29]. Among them, Ach and SP are excitatory neurotransmitters that promote bowel motility and speed defecation, while NO and VIP are inhibitory neurotransmitters that relax the gastrointestinal tract and inhibit bowel movement [3,30].…”
Section: Discussionmentioning
confidence: 99%
“…After integration of the intestinal bacteria gene and host gene, the extrinsic primary sensory neurons stimulated by neurotransmitters release signals again. These signals are uploaded to the central nervous system, and the information is integrated and sent to the target organ, thus completing the BGMA [3,8].…”
Section: Introductionmentioning
confidence: 99%
“…The important role of this membrane-penetrating aquaporin (AQP) is to help water molecules pass through the cell membrane rapidly [10]. It has been proven through experiments [11] that injecting vasoactive intestinal peptide (VIP) into rats with diarrhea increases the VIP expression in serum and intestinal tissues, and the protein expression of AQP is regulated by VIP activity, and the signal pathway of VIP/PKA/AQP in colon epithelial cells is affected, changing the molecular mechanism of intestinal water metabolism and causing the disappearance of diarrheal symptoms [8,12].…”
Section: Introductionmentioning
confidence: 99%
“…The compound diphenoxylate is a kind of drug used to treat functional diarrhea; it can block receptors on intestinal mucosa and reduce intestinal peristalsis to delay intestinal contents; however, it can lead to constipation under normal conditions [16]. According to this pharmacological function, diphenoxylate can be used to induce constipation in mice to establish an animal constipation model, which became an important experimental method to examine the effects of food on inhibiting constipation [17]. As a common fermented food in China, Shuidouchi is similar to Japanese natto.…”
Section: Introductionmentioning
confidence: 99%